2020
DOI: 10.3390/cryst10110958
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Study of EMBr Effects on the Detrimental Dynamic Distortion Phenomenon in a Funnel Thin Slab Mold

Abstract: The turbulent phenomena occurring in the thin slab mold affect the final product quality. Therefore, it is essential to carry out studies to understand and control their occurrence. Current research aims to study the electromagnetic brake (EMBr) effects on the flow patterns in a funnel thin slab mold. The objective is to prevent the detrimental phenomenon known as dynamic distortions (DD) of the flow, applying the EMBr in the typical horizontal position (H-EMBr) and a new vertical position close to the narrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Garcia-Hernandez et al observed perturbations of the meniscus level in thin slab castings due to periodic flow alterations and refer to this turbulent behavior of the flow under the term dynamic distortions (DDs). [21] The authors investigated whether and how the horizontal and vertical EMBrs can be applied to prevent the occurrence of DDs at the meniscus. While there seems to be some success in the case of the horizontal EMBr, the authors surprisingly failed to show a way to prevent or control the DD phenomenon using the vertical EMBr.…”
Section: Ensuring the Quality Of Continuous Cast (Cc)mentioning
confidence: 99%
“…Garcia-Hernandez et al observed perturbations of the meniscus level in thin slab castings due to periodic flow alterations and refer to this turbulent behavior of the flow under the term dynamic distortions (DDs). [21] The authors investigated whether and how the horizontal and vertical EMBrs can be applied to prevent the occurrence of DDs at the meniscus. While there seems to be some success in the case of the horizontal EMBr, the authors surprisingly failed to show a way to prevent or control the DD phenomenon using the vertical EMBr.…”
Section: Ensuring the Quality Of Continuous Cast (Cc)mentioning
confidence: 99%
“…However, a series of recent studies has revealed the details of its complex topology, which leads to the entrainment of the quiescent melt into the formation of the reverse zones near the jets and in the upper region of the CC mold [8][9][10]. The flow pattern in the mold, the superheat distribution and the melt solidification are significantly altered under the EMBr during the continuous casting (CC) process [11][12][13][14][15][16][17]. The influence of the applied magnetic field on the asymmetric flow inside a TSC mold due to the partial SEN blockage was recently presented by the authors including effects on the solidification profiles [18].…”
Section: Introductionmentioning
confidence: 99%
“…These include the effects of liquid steel mass reduction due to solidification [8], shell formation, model bottom, and electromagnetic brake [9,10], and its effect on the level of fluctuation heights in the mold [11,12]. In this case, electromagnetic fields have emerged as powerful tools for addressing current problems in thin-slab continuous casting processes in the iron and steel industry [13]. In particular, the electromagnetic brake adopted a new magnet type specially designed for the thin-slab casting funnel-shaped mold [14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, authors like Wang et al [15] studied predicting transient fields in the caster using a large eddy simulation and an enthalpy-porosity method; such a method helps predict the solidification shell in addition to increasing the possibility of washing the solidified steel crust [16] and possible wire breakage [17]. Also, there are other consequences to consider: slag trapping toward the sinus of liquid metal [18,19], slag droplets into steel volume [20], the movement of inclusions [13], and the possible reoxidation of the liquid steel due to the opening of the slag [21,22], as has been shown through numerical simulation techniques using colorimetry and PIV [23].…”
Section: Introductionmentioning
confidence: 99%